Analisis Efektifitas Distribusi Produk Guna Meminimalisir Bullwhip Effect dengan Menggunakan Metode Peramalan pada Distributor PT. Kosmetika Global Indonesia - Rico Ari Kurniawan; Achmad Misbah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The bullwhip effect phenomenon occurs due to differences in demand patterns between distributors and retailers, causing overstock. This happened to Distributor PT. INDONESIAN GLOBAL COSMETICS where companies experience overstock and sometimes stock shortages, due to information distortion between companies, distributors and retailers due to different demand predictions. Therefore, the author conducted research to minimize the bullwhip effect phenomenon using the forecasting method in Microsoft Excel software. The data used in this research is demand and sales data for the period July 2023 to June 2024 for facial wash beauty products. Data processing is carried out by calculating the bullwhip effect value for the product. Next, carry out forecasting calculations. Then a comparison of the bullwhip effect values ​​was carried out as an improvement with this forecasting method. Furthermore, the results obtained from this research are the magnitude of the bullwhip effect in the PT Distributor supply chain. INDONESIAN GLOBAL COSMETICS has a value of 1.012 and is greater than 1, which means there has been a bullwhip effect in the observed supply chain. From the results of the analysis, it is known that the causes of the bullwhip effect include the absence of a user system and strategy in forecasting needs, unmeasured inventory or shortages of inventory, fluctuating prices, order sizes and grace periods for order fulfillment, as well as estimated inventory results in the following month of 992 .71 pcs with a minimum of 929.40 pcs and a maximum of 1056.02 pcs. Ways that may be effective in reducing the bullwhip effect that occur include managing product availability well, namely by implementing controlled forecasting, selling product orders and also the accuracy of information from product sales so that business owners will easily calculate forecasting values ​​for the coming period.